Clarifying the boundary conditions of value creation within dynamic capabilities framework: a grafting approach - Björn Michaelis; Shalini Rogbeer; Lars Schweizer; Zafer Özleblebici (Review of Managerial Science, 2020)
This study extends dynamic capabilities research by examining the underlying and fundamental concepts of capabilities, resource allocation, fungibility, and environmental change with respect to value creation and appropriation (VCA). Scholars generally assume that VCA depends on the amount of resources allocated to generate future capabilities. We diverge from this ability-performance tautology and instead ground dynamic capabilities in a resource allocation framework. By introducing two boundary conditions, we suggest that environmental change and fungibility between current and dynamic capabilities determine whether resource allocation leads to VCA. We believe that our findings not only represent a fruitful path for future research by strategy and organization scholars, but also provide an important contribution to our knowledge of managing resources in dynamic environments to create future capabilities.
Keywords: M19; M29; 650; Dynamic capabilities; Environmental change; Fungibility; Resource allocation; Value creation